2022
DOI: 10.3389/fnbeh.2022.936105
|View full text |Cite
|
Sign up to set email alerts
|

Aggression, Aggression-Related Psychopathologies and Their Models

Abstract: Neural mechanisms of aggression and violence are often studied in the laboratory by means of animal models. A multitude of such models were developed over the last decades, which, however, were rarely if ever compared systematically from a psychopathological perspective. By overviewing the main models, I show here that the classical ones exploited the natural tendency of animals to defend their territory, to fight for social rank, to defend themselves from imminent dangers and to defend their pups. All these f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…Aggression comprises a suite of agonistic behavioural interactions; thus, various species-specific relevant signals, including danger and emotional stressors, are transduced by sensory afferents to the central nervous system (CNS) where this information is processed by the limbic neurocircuitry [ 99 , 100 ]. Data from animal and human studies suggested several key brain regions, primarily in the limbic system, associated with aggression and depressive syndromes [ 101 ].…”
Section: Neuroanatomical Basis Of Aggression In Humans and Rodents In...mentioning
confidence: 99%
See 1 more Smart Citation
“…Aggression comprises a suite of agonistic behavioural interactions; thus, various species-specific relevant signals, including danger and emotional stressors, are transduced by sensory afferents to the central nervous system (CNS) where this information is processed by the limbic neurocircuitry [ 99 , 100 ]. Data from animal and human studies suggested several key brain regions, primarily in the limbic system, associated with aggression and depressive syndromes [ 101 ].…”
Section: Neuroanatomical Basis Of Aggression In Humans and Rodents In...mentioning
confidence: 99%
“…The amygdala is generally regarded as a key brain structure regulating aggressive behaviour [ 101 , 102 , 103 ]. It mediates fear and defensive responses [ 104 ] and is important in the processing of emotionally adverse events [ 105 ].…”
Section: Neuroanatomical Basis Of Aggression In Humans and Rodents In...mentioning
confidence: 99%
“…Even when the intruder surrendered and became immobile, the resident with bilateral CeA activation slowly approached and bit the intruder. Thus, the aggression observed in the MS group might reflect abnormal aggression beyond the need to defend territory as defined by Haller (Haller, 2018, 2022).…”
Section: Discussionmentioning
confidence: 88%
“…Thus, the aggression observed in the MS group might reflect abnormal aggression beyond the need to defend territory as defined by Haller (Haller, 2018(Haller, , 2022.…”
Section: Discussionmentioning
confidence: 92%
“…Of note, all the patients described herein manifested a hyperactive form of delirium, exhibiting verbal and physical aggressiveness towards the health workers. Verbal and physical aggressiveness towards health workers can be considered, in psychopathological terms, a form of hetero-aggressiveness or heterodirect aggressiveness, which is a feature of hyperactive delirium, that is characterized itself by an aggressive behavior, according to DSM-5 (87)(88)(89)(90). However, it is possible that some cases of hypoactive delirium have passed undiagnosed and have been resolved without the use of medications.…”
Section: Discussionmentioning
confidence: 99%